[/IMG]
Hello guys, need your help!!
From the example above, they tried to solve that differential equation, I didn't understand why in #2 step they have -x ?
I mean this (dy)/(y-6) = -x(dx)
How did they get that -x(dx)?
This is using seperation of variables (with a slight abuse of notation) we have:
dy/dx = x (6-y),
so:
dy/(6-y) = x dx
Now we could work with this but it is a bit more convienient to have the
coefficient of y in the denominator on the left to be +1, so we multiply
through by -1 to get:
dy/(y-6) = -x dx
RonL